2018
DOI: 10.1002/celc.201801513
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polypyrrole Coated Hollow NiCo2O4 Microspheres as Anode Material with Improved Pseudocapacitive Contribution and Enhanced Conductivity for Lithium‐Ion Batteries

Abstract: Conductive polypyrrole (PPy) coated urchin-like hollow NiCo 2 O 4 (NCO) porous microspheres (NCO@PPy) were synthesized by an easy and cost-effective method. The NCO@PPy shows improved cycling stability and rate capability in comparison with the pure NiCo 2 O 4 when used as anode material for lithium-ion batteries. In order to undersatnd the improvement of electrochemical performance of NCO@PPy, kinetic parameters and the lithium storage mechanism are investigated by EIS spectra and sweep voltammetry measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Different from NCM, sample PPy5 exhibits a conspicuous N 1s signal at about 400.0 eV (Figure d). This photoelectron signal is originated from the nitrogen element in the PPy . Combining the analysis of XPS, TEM, Raman and FTIR, it can be reasonably concluded that the PPy was successful coated on the surface of NCM, but did not change the the valence state of cations.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Different from NCM, sample PPy5 exhibits a conspicuous N 1s signal at about 400.0 eV (Figure d). This photoelectron signal is originated from the nitrogen element in the PPy . Combining the analysis of XPS, TEM, Raman and FTIR, it can be reasonably concluded that the PPy was successful coated on the surface of NCM, but did not change the the valence state of cations.…”
Section: Resultsmentioning
confidence: 86%
“…Two peaks at 476 and 592 cm −1 are assigned to the bending E g and stretching A 1g modes of layered LiMO 2 . [36,37] Different from NCM, two extra broad peaks at around 1350 and 1585 cm −1 observed in the Raman spectrum of PPy5 are ascribed to C=C stretching and the anti‐symmetrical C−N stretching mode of PPy . To further ascertain the presence of PPy, the samples NCM and PPy5 were also characterized by FT‐IR spectroscopy (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The carbon materials including reduced graphene oxide (rGO) and carbon nanotubes (CNT) . Except the methods above, conductive polymer serves multiple functions in the composite when they are used in anode such as polypyrrole (PPy) and polyaniline …”
Section: Introductionmentioning
confidence: 99%
“…In this line, some ternary oxides have been developed, such as ZnCo 2 O 4 , [13][14][15] CoFe 2 O 4 , [16][17][18] and NiCo 2 O 4 . [19][20][21] Among them, ZnCo 2 O 4 (ZCO) is very promising since conversion and alloy combined charge storage mechanism occurs upon lithiation. This material delivers high specific capacity, theoretically 789 mA h g −1 with 7e − per formula unit ( pfu).…”
Section: Introductionmentioning
confidence: 99%